2003
DOI: 10.1097/00005537-200312000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Topical Ciprofloxacin/Dexamethasone is Superior to Ciprofloxacin Alone in Pediatric Patients with Acute Otitis Media and Otorrhea through Tympanostomy Tubes

Abstract: Topical otic treatment with ciprofloxacin/dexamethasone is superior to treatment with ciprofloxacin alone and results in a faster clinical resolution in children with AOMT. The contribution of the corticosteroid in achieving a 20% reduction (1.1 day) in time to cessation of otorrhea is clinically meaningful and represents an important advance over single-agent antibiotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
53
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 21 publications
4
53
1
2
Order By: Relevance
“…4,5,16,17 The present study shows that the addition of the corticosteroid dexamethasone to the fluoroquinolone ciprofloxacin achieves superior rates of clinical cure and microbiologic success, results in fewer treatment failures, and provides earlier resolution of AOMT compared with treatment with the single-agent fluoroquinolone ofloxacin. In this regard, the findings confirm our earlier clinical report of ciprofloxacin/dexamethasone versus ciprofloxacin 15 and in experimental animal studies showing that antibiotic/dexamethasone combinations are more effective than antibiotic therapy alone in resolving otorrhea in a primate model of CSOM 14 and in reducing and preventing persistent middle ear mucosal changes in rats with experimental AOM. 20 In the current AOMT study in children aged Ն6 months to 12 years, we show that a 7-day course of ciprofloxacin/dexamethasone (4 drops twice daily, 56 total drops) with less total drug administered is superior to a 10-day course of ofloxacin (5 drops twice daily, 100 total drops) for clinical cure, microbial eradication, and treatment failures.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…4,5,16,17 The present study shows that the addition of the corticosteroid dexamethasone to the fluoroquinolone ciprofloxacin achieves superior rates of clinical cure and microbiologic success, results in fewer treatment failures, and provides earlier resolution of AOMT compared with treatment with the single-agent fluoroquinolone ofloxacin. In this regard, the findings confirm our earlier clinical report of ciprofloxacin/dexamethasone versus ciprofloxacin 15 and in experimental animal studies showing that antibiotic/dexamethasone combinations are more effective than antibiotic therapy alone in resolving otorrhea in a primate model of CSOM 14 and in reducing and preventing persistent middle ear mucosal changes in rats with experimental AOM. 20 In the current AOMT study in children aged Ն6 months to 12 years, we show that a 7-day course of ciprofloxacin/dexamethasone (4 drops twice daily, 56 total drops) with less total drug administered is superior to a 10-day course of ofloxacin (5 drops twice daily, 100 total drops) for clinical cure, microbial eradication, and treatment failures.…”
Section: Discussionsupporting
confidence: 88%
“…15 Otorrhea resolved more rapidly with the combination preparation than with ciprofloxacin alone and produced significantly greater clinical responses early after completion of a 7-day course of treatment. 15 The present study was designed to evaluate further the efficacy and the safety of the topical ciprofloxacin/ dexamethasone combination by comparing it with the related fluoroquinolone ofloxacin administered alone in children with AOMT. Topical ofloxacin was chosen as the comparator for this study because of its reported efficacy and safety in ear infections, including AOMT, 16,17 CSOM, 18 and acute otitis externa.…”
mentioning
confidence: 95%
“…It has also shown that combination therapy including dexamethasone has been to be more effective than antibiotic alone in the treatment of acute otitis media and otorrhea through a patent tympanostomy tube. The addition of dexamethasone is also more effective in the reduction of granulation tissue than antibiotic therapy alone [12,15,21]. In this study, we have found that ITD is also more effective than conventional therapy in the reduction of hearing loses and middle ear pressure in this study.…”
Section: Discussionsupporting
confidence: 54%
“…Ciprodex demonstrates no ototoxicity in animal studies [15] and in clinical trials with patients with TTs, ciprofloxacin demonstrates a favorable safety profile with no detrimental effects on hearing [16][17][18]. One clinical question is whether the steroid component will slow healing of the tympanic membrane, resulting in an increase number of tympanic membrane perforations.…”
Section: Discussionmentioning
confidence: 99%